Legal Crisis and Trends of Mass Violence in Indonesia - Utari, Indah Sri (JILS (Journal of Indonesian Legal Studies), 2019)
This study aims to explore the reasons for the problems that trigger broader mass violence, both in the form of structural conditions in society as well as the factors that trigger crime and social dynamics that trigger mass violence. The main research method used is a qualitative approach to the type of research criminally. The results of the research show that at the end of this time the social integration ties that are owned by the community are not so strong that the provocateurs of violence in the community are able to ravage the solidarity that is intertwined within the community. The joints of democratic society which should function to normalize normal social-political interaction relations, in the end actually caused mass violence, such conditions create anomistic situations occur, members of society both individually and in groups are so easy to play their own way. Therefore, the legal institutions as a formal rule of the game and apply to everyone, are experiencing a crisis of authority. The fundamental reason why this happens is that there are often different legal decisions against each violator of the law. As a result, there is no certainty that the law is truly an objective norm that applies to all. People who have been relatively safe in the normalcy of their environment have turned into mutual suspicion. As a result of this, collective disappointment arises over legal institutions, so that losing motivation to obey the law people tend not to believe in the legal process, which results in acts of mass violence in the community.